Tinjauan Hukum Terhadap Pelaksanaan Investasi Jual Beli Property Apartemen Meikarta - Efrat, Christian; Apriani, Rani (Jurnal Ilmiah Wahana Pendidikan, 2024)
The development of the times has had a broad impact on the life of the nation and state. Especially developments in the industrial economic sector. It cannot be denied that the rapid pace of economic development causes people's power to invest to also increase. As the economy progresses in the investment sector, the role of each party is needed to support investment and/or capital investment programs as stated in Legislative Regulation No. 25 of 2007 concerning Capital Investment. The basic aim is to increase the country's economic speed in order to create a healthy business climate. Meikarta, as a form of developer negligence in carrying out its obligations, is an interesting matter to discuss. Moreover, the legal relationship between consumers who invest in the property sector is an interesting legal relationship to dissect using a civil law approach and legal responsibility for PT's actions. MSU as developer. The stalled development and the PKPU Bankruptcy lawsuit at the Central Jakarta Commercial Court have added to the series of investment controversies in the property sector. Keywords: Investment, Meikarta, Legal Responsibility